Of mind and matter: the archive as object. Issue 1 (2nd January 2018) - Lester, Peter
Abstract: Archives are not only sources of evidence and information; they are also material objects with physical, tangible characteristics such as size, weight and colour. Moreover, the way in which researchers and visitors to archives respond to them may not just be intellectual, but sensory and emotional as well. Despite this, it is the informational content of archives which is routinely given prominence over their material properties. In this article, I discuss some of the recent literature regarding the physical and material properties of archives and consider why and how their materiality is often unacknowledged. In considering our response to archives, I argue that our engagement with archival records is a holistic experience, in which cognitive and physical reactions shape one another. Using the concept of the 'body schema' as a tool to understand how these reactions occur, the paper frames these discussions around specific examples of exhibited archives at the Petit Palais in Paris.